Implementing A Quality Learning In Schools - Andi Warisno (Ar-Raniry: International Journal of Islamic Studies, 2018)
A quality learning process is a process of learning based on continuous improvement. The quality can be measured from the quality of inputs, processes, and outputs. In itsimplementation, it requires a culture of quality that grows from all parties: teachers,school principals, students, staff, cleaning service, and all of the school’s components.By improving the quality of learning, it means we have improved the quality ofeducation as a whole.